2014
DOI: 10.1016/j.numecd.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

PPARα gene polymorphisms modulate the association between physical activity and cardiometabolic risk

Abstract: Background and Aims Habitual physical activity is understood to help prevent type 2 diabetes and atherosclerotic cardiovascular disease via beneficial effects on both metabolism and the vascular system. However, individuals do not have uniform cardiometabolic responses to physical activity. Here we explore the extent to which variation in the proliferator-activated receptor-alpha (PPARA) gene, which modulates carbohydrate and lipid metabolism, vascular function, and inflammation, predicts the overall cardiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In these studies, C allele homozygotes had a significantly greater left ventricular mass index compared with G allele homozygotes and C allele heterozygotes, which was greater in hypertensive subjects [133]. Moreover, Halder et al found that the presence of the G allele of rs135542 was associated with higher cardiometabolic risk [134]. Another report found a significant association between rs135551 and myocardial infarction and an association trend between rs135543 and myocardial infarction [135].…”
Section: Association Of Pparα Polymorphisms With Cardiovascular Diseasesmentioning
confidence: 95%
“…In these studies, C allele homozygotes had a significantly greater left ventricular mass index compared with G allele homozygotes and C allele heterozygotes, which was greater in hypertensive subjects [133]. Moreover, Halder et al found that the presence of the G allele of rs135542 was associated with higher cardiometabolic risk [134]. Another report found a significant association between rs135551 and myocardial infarction and an association trend between rs135543 and myocardial infarction [135].…”
Section: Association Of Pparα Polymorphisms With Cardiovascular Diseasesmentioning
confidence: 95%
“…Halder et al . [ 23 ] showed rs135542 to influence habitual physical activity and cardiometabolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PPARα participates in mitochondrial-mediated energy metabolism [ 51 ] and can also regulate the synthesis of very low-density lipoproteins to improve blood lipids [ 52 ]. In many clinical studies, PPARα has also been linked to the start of cardiovascular disease, atherosclerotic alterations, and hypertension in numerous clinical trials [ 53 , 54 , 55 , 56 ]. In the current research, the exploration and clinical intervention of PPAR α also focuses on PO.…”
Section: Discussionmentioning
confidence: 99%